Pengembangan Jiwa Kewirausahaan RISMA Masjid di Takwa Gebang - Mutia Azizah Nuriana; Fitri Apqorinur'Aeni (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2026)
Remaja Islam Masjid (RISMA) plays a crucial role in supporting the mosque's role as a center for community development and empowerment, including in the economic sector. However, the economic potential of RISMA members is often underdeveloped due to low levels of entrepreneurial literacy, limited business experience, and a lack of ongoing mentoring. Most RISMA activities focus on religious activities, leaving economic empowerment a primary focus. To address these issues, a community service activity was conducted at the At Taqwa Gebang Mosque using the Participatory Action Research (PAR) method. This method actively involved RISMA members in problem identification, entrepreneurship training, business mentoring, and joint evaluation. The results of the activities showed an increase in entrepreneurial understanding, the emergence of mosque-based business initiatives, and increased independence and participation among RISMA members.